Pemanfaatan Berbagai Jenis Bahan Organik sebagai Mulsa untuk Pengendalian Gulma di Areal Budidaya Tanaman - Vira Irma Sari (JURNAL CITRA WIDYA EDUKASI, 2018)
Weed control is based on the technical culture in terms of the ecology of plants and weeds, where control is aimed to create conditions favorable environment for plant growth, but detrimental to weeds. Mulching is one of weed control in technical culture which can utilize organic material around the area of ​​cultivation. This study aimed to get an alternative organic materials that can be used as mulch for weed control. The experimental design used was completely randomized design non factorial with two replications. The treatments tested were the provision of various types of mulch of organic material. The results showed that the provision of various types of organic material as mulch significantly affect the ability to grow and dry weight of weeds. Mulch is best found in rice husks and did not differ significantly by mulching oil palm fronds, dried leaves, plastic and sacks. Mulching with organic materials to effectively control various weeds in the cultivation area because it can inhibit weed to get the elements needed. Mulching organic produce growing power of weeds that are not significantly different from anorganic mulch used is sacks and plastic.